Sponsorisasi pada team olahraga - Ryan Johan Sembiring; Donant Alananto Iskandar (Jurnal Riset Manajemen dan Bisnis, 2022)
Sponsors have become one of the essential factors in sports activities, and their role as one of the critical aspects in implementing sports activities cannot be denied. Especially for sports teams, sponsors can provide additional funding that can support operational activities. Meanwhile, from the perspective of sponsors, companies' involvement in providing their support is based more on promotional strategies to expand the symbolic value of sponsors. This brief commentary briefly describes sponsorship, marketing, and future study opportunities.